2019
DOI: 10.3762/bjoc.15.61
|View full text |Cite
|
Sign up to set email alerts
|

The LANCA three-component reaction to highly substituted β-ketoenamides – versatile intermediates for the synthesis of functionalized pyridine, pyrimidine, oxazole and quinoxaline derivatives

Abstract: The LANCA three-component reaction of lithiated alkoxyallenes LA, nitriles N and carboxylic acids CA leads to β-ketoenamides KE in good to excellent yields. The scope of this reaction is very broad and almost all types of nitriles and carboxylic acids have successfully been used. The alkoxy group introduced via the allene component is also variable and hence the subsequent transformation of this substituent into a hydroxy group can be performed under different conditions. Enantiopure nitriles or carboxylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As mild Lewis bases, pyridine N-oxides can result in activating Lewis acid parts of molecules and also increasing the reactivity of nucleophilic part toward different reactions with electrophiles. [115][116][117][118] Pyridines have been highly significant in catalyzing reactions, as reported in a study by Yoshida and coworkers. In this regard, they reported that when TBDPSCl, DIPEA, and pyrrolidinopyridine N-oxide (PPYO) catalyst are combined, it would bring about silylating different secondary alcohols in CH 2 Cl 2 at r.t. with excellent yields.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 83%
“…As mild Lewis bases, pyridine N-oxides can result in activating Lewis acid parts of molecules and also increasing the reactivity of nucleophilic part toward different reactions with electrophiles. [115][116][117][118] Pyridines have been highly significant in catalyzing reactions, as reported in a study by Yoshida and coworkers. In this regard, they reported that when TBDPSCl, DIPEA, and pyrrolidinopyridine N-oxide (PPYO) catalyst are combined, it would bring about silylating different secondary alcohols in CH 2 Cl 2 at r.t. with excellent yields.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 83%
“…A very interesting option to highly substituted pyrimidines and other functionalized heterocycles is offered by the LANCA three-component approach [LANCA = LA (lithiated alkoxyallenes) + N (nitriles) + CA (carboxylic acids)] to β-alkoxy-β-ketoenamides A (Scheme 1 ), discovered and developed by our group. 6 7 The reaction of these versatile intermediates with hydroxylamine hydrochloride smoothly provides 4-methyl-substituted pyrimidine N -oxides B under mild conditions, 8 whereas the heating of A with ammonium salts furnishes the corresponding pyrimidine derivatives C in good yields (Scheme 1 ). 9 The subsequent Boekelheide rearrangement of B with carboxylic acid anhydrides converts these compounds into 4-carbonyloxy-substituted pyrimidine derivatives, 10 and, after saponification, hydroxymethyl-substituted pyrimidines D are available with good efficiency (Scheme 1 ).…”
Section: Table 1 Oxidation Of 4-hydroxymethyl-substitut...mentioning
confidence: 99%
“…Their substitution pattern allowed a variety of subsequent reactions leading to comprehensive libraries of heterocycles. [9] The successful application of β-alkoxy-β-ketoenamides for the synthesis of hundreds of new compounds motivated our group to study the behavior of simple β-ketoenamides (Scheme 1, lower part) which are very easily available in two steps from ammonia, 1,3diketones and carboxylic acids. Analogous cyclization reactions led indeed to formation of pyridine, bipyridine, terpyridine and pyrimidine derivatives in good yields.…”
Section: Introductionmentioning
confidence: 99%